(untitled) (Nepal Journal of Epidemiology, 2011)
Background: The perception of nonalcoholic fatty liver disease (NAFLD) as an infrequent and benign condition is swiftly altering in developing countries as there has been an upsurge in non alcoholic fatty liver disease in Asia-Pacific region. NAFLD develops across all age groups and societies and is recognized to occur in 14%–30% of the common population. The foremost risk factors for NAFLD such as central obesity, diabetes mellitus, insulin resistance, dyslipidemia, hypertension, hypertriglyceridemia are currently predominant and puts a very large population at risk of evolving hepatic steatosis in the coming decades. Material and Methods: It was a hospital based case control study carried out in the Department of Biochemistry of Manipal Teaching Hospital, Pokhara, Nepal between 1st January 2010 and 31st Dec 2010. The variables collected were age, gender, fasting blood glucose, total cholesterol, low density lipoproteins, triglycerides, high density lipoproteins, very low density lipoproteins, aspartate transaminase, alanine transaminase. Results: Of the 200 patients of non alcoholic fatty liver disease patients with diabetes mellitus, all the variables except triglycerides shows insignificant disparity in relation to gender. The perceptible difference was observed in mean values of triglycerides for cases of NALFD between diabetes (218.25 ± SD 73.68) and non diabetic subjects (177.54 ± SD73.45) (p=.0001). The mean values of HDL did not illustrate much difference in cases of NALFD with diabetes (41.54 ± SD2.13) and non diabetic subjects (44.24 ± SD2.05). Conclusion: Public health initiatives are undoubtedly of the essence to halt or turn around the global ’diabesity’ pandemic, the causal basis of NAFLD. Management of patients with NAFLD should be aimed at treating metabolic risk factors such as hyperglycemia and hypertriglyceridemia. Successful lifestyle adaptation with increased exercise and decreased food intake is able to remove the accumulation of liver fat and can reverse insulin resistance. Key words: Hepatic steatosis; Diabetes mellitus; Risk factors; Nepal. DOI: http://dx.doi.org/10.3126/nje.v1i2.5135 Nepal Journal of Epidemiology 2011;1 (2):51-56